Development of newer adsorbents: activated carbons derived from carbonized cassia fistula - Sorokhaibam, Laxmi Gayatri; Bhandari, Vinay M.; Salvi, Monal S.; Jain, Saijal; Hadawale, Snehal D.; Ranade, Vivek V. (Industrial & Engineering Chemistry Research, 2015)
Development of newer adsorbent materials, especially from biomass, is most crucial to sustain growth of otherwise well established adsorption processes that already have hundreds of commercial adsorbents in practice. In the present study, newer adsorbents and their potential-carbonaceous adsorbents derived from the whole fruit of Cassia fistula (Golden shower) have been reported for applications in environmental pollution control using natural, renewable biomass as precursor. The potential of different forms of the derived adsorbents produced by thermal and chemical activation was examined for two representative cases, desulfurization of transportation fuels and wastewater treatment. The adsorbents were characterized by FTIR, XRD, XPS, and SEM techniques that indicate specific characteristics useful as an adsorbent. A successful application in the real industrial wastewater treatment and comparison with well recognized commercial adsorbents clearly highlights the utility of the developed newer adsorbents in separation science and technology.

Differentiating process performance of various coagulants in removal of congo red and orange G dyes - Prajapati, Kavita; Sorokhaibam, Laxmi Gayatri; Bhandari, Vinay M.; Killedar, D. J.; Ranade, Vivek V. (International Journal of Chemical Reactor Engineering, 2016)
Two refractory azo dyes-Congo red and Orange G, especially at high concentrations were subjected to coagulation with different conventional coagulants and newer formulations developed from Aluminum sulfate, Iron (III) chloride, Aluminium chloride, Poly diallydimethylammonium chloride (Poly DADMAC) and Poly Aluminium Chloride (PAC). The highest COD reduction of 99 % was obtained with PAC SAB 18 (Powder Grade PAC) for Congo red at pH 4.5 while the color removal of 99 % was achieved with almost all the coagulants in the present study at specific pH within 3-8. The optimum dose for the iron-based coagulant is 200 mg/L while that of aluminum-based coagulants and PAC is 150-200 mg/L. Results showed that Orange G was more difficult to remove with a maximum COD removal of 65 % and 35 % color removal using various formulations. The combinational formulations of inorganic-inorganic and inorganic- organic produced a substantial enhancement in COD and color removal and reduced sludge. PAC-Fe30/70 produces the minimum sludge of 50 mL/g on Congo red. pH in the range 3-9 showed high reductions in COD and color (90-99 %) for Congo red while jerky rise in COD and color reduction was observed in the case of Orange G after pH 9. An attempt to understand the dye coagulation mechanism has been made based on the specific difference in dye structure and cation speciation.
Keywords: coagulation; Congo red; dye removal; Orange G; Wastewater treatment

Destroying antimicrobial resistant bacteria (AMR) and difficult, opportunistic pathogen using cavitation and natural oils/plant extract - Mane, Maya B.; Bhandari, Vinay M.; Balapure, Kshama; Ranade, Vivek V. (Ultrasonics Sonochemistry, 2020)
The present study reports, for the first time, a new and techno-economic strategy for effective removal of antimicrobial resistant bacteria (AMR) and difficult, opportunistic pathogen using cavitation and natural oils/plant extract. A hybrid methodology using natural oils of known health benefits has been discussed in combination with conventional physico-chemical method of hydrodynamic cavitation that not only provides efficient and effective water disinfection, but also eliminates harmful effects of conventional methods such as formation of disinfection by-products apart from reducing cost of treatment. A proof-of concept is demonstrated by achieving exceptionally high rates for practically complete removal of antimicrobial resistant (AMR) and relatively less researched, gram-negative opportunistic pathogen, Pseudomonas aeruginosa and gram-positive methicillin resistant, Staphylococcus aureus using a natural oil-Peppermint oil and two different cavitating reactors employing vortex flow (vortex diode) and linear flow (orifice) for hydrodynamic cavitation. > 99% disinfection could be obtained, typically in less than 10 min, using vortex diode with operating pressure drop of 1 bar and low dose of 0.1% peppermint oil as an additive, depicting very high rates of disinfection. The rate of disinfection can be further increased by using simple aeration which can result in significant lowering of oil dose. The conventional device, orifice requires relatively higher pressure drop of 2 bar and comparatively more time (similar to 20 min) for disinfection. The cost of the disinfection was also found to be significantly lower compared to most conventional processes indicating techno-economic feasibility in employing the developed hybrid method of disinfection for effectively eliminating bacteria including AMR bacteria from water. The developed approach not only highlights importance of going back to nature for not just conventional water disinfection, but also for eliminating hazardous AMR bacteria and may also find utility in many other applications for the removal of antimicrobial bacteria.
Keywords: AMR bacteria; Cavitation; Disinfection; Oil; Water treatment

Design of hydrodynamic cavitation assisted intensified tertiary treatment unit for effective degradation of organic micropollutants in pharmaceutical industrial effluent: a case study with triclosan - Mishra, Birupakshya; Mukherjee, Anupam; Mullick, Aditi; Bhandari, Vinay M.; Moulik, Siddhartha (Journal of Water Process Engineering, 2022)
Increasing occurrence of micropollutants and trace amount of persistent organic contaminants (POC's) in the wastewater streams even after the well-established conventional treatment is a threat to human health, aquatic entities, and constitute a formidable challenge for the ecological security. In this regard, hydrodynamic cavi-tation based advanced oxidation treatment has attracted extensive attention towards removal of such micro scale pollutants from wastewater streams in the present scenario. Hence, the present work demonstrates the design and application of a rotating hydrodynamic cavitation (RHC) reactor with stator-rotor arrangement for effective degradation of organic micropollutants (triclosan being taken as the target pollutant) from tertiary effluents occurring in the pharmaceutical sector. The process performance was evaluated through optimization of geo-metric parameters of the reactor, various operating parameters as well as by studying the sole and synergistic performance of the HC process combined with other AOPs. The maximum degradation of Triclosan (TCS) ach-ieved by RHC alone was found to be 35.2 % and in synergism, with ozone, a maximum of 97.6 % degradation was observed. Further, to ensure the mineralization of the components, total organic carbon (TOC) contents of the samples were measured and the degradation pathway was predicted through LC-MS analysis. The techno-economic feasibility of the process were understood through economic and energetic analysis and technology transfer was done for replicating the same study for a pilot scale reactor.
Keywords: Advanced oxidation process; Hydrodynamic cavitation; Micropollutant; Pharmaceutical effluent; Tertiary treatment

Development of multipurpose biomass-derived adsorbents using Coccinia grandis for removal of contaminants - Raj, Surabhi S.; Mane, Maya B.; Thanekar, Pooja; Balapure, Kshama; Bhandari, Vinay M. (Clean Technologies and Environmental Policies, 2023)
The present study is an attempt to develop newer multipurpose biomass-derived adsorbents for water and wastewater treatment; biomass that are easily available, renewable and most importantly, sustainable. A model adsorbent was developed using Coccinia grandis (CG, Ivy gourd) and further modified by impregnating copper nanoparticles (CG-Cu). The adsorbent characterization was done for evaluating surface morphology, surface area and metal modification. The utility of the newer adsorbents was established for the removal of different contaminants such as dyes (cationic Malachite Green, anionic Congo Red and fluorescent cationic Rhodamine B), Active Pharmaceutical Ingredient pollutant (Ciprofloxacin) and also for the removal of pathogenic bacteria, Gram-negative Escherichia coli. Both CG and CG-Cu bio-nanocomposite were highly effective in removal of different contaminants, 99% dye removal for Malachite Green, with a high adsorption capacity of 49 mg/g, higher than that for commercial activated charcoal whereas for all other dyes, the performance of CG-Cu was similar. The isotherm studies indicated multilayer adsorption, in general. A good adsorption capacity of 10.8 mg/g was also observed for the removal of ciprofloxacin. The combined effect of the bio-nanocomposite, CG-Cu was impressive and 100% disinfection was achieved within 10 min, due to the antimicrobial activity of Cu and oxidation effect of reactive oxygen species enhancing the disinfection.Graphical abstractMultipurpose biomass derived adsorbents using Coccinia grandis for removal of contaminants
Keywords: Adsorption; Biomass; Disinfection; dye removal; nanomaterial; Separation

Dual activity cavitation reactors for increased efficacy in degradation of refractory pollutants-A case study on cephalexin degradation - Dixit, Divya; Thanekar, Pooja; Bhandari, Vinay M. (Chemical Engineering Research & Design, 2023)
The present work discloses a new form of cavitation processes using reactors of dual activity for increased efficiency. A proof of concept is established for the degradation of a refractory pollutant-cephalexin using both conventional and dual function cavitation reactors for the first time using acoustic and hydrodynamic cavitation (HC). A vortex diode as a cavitating device was employed for HC using aluminium as a non-catalytic and copper as dual function device for providing additional catalytic effect. The process in-tensification using hydrogen peroxide (H2O2) coupled with the dual function devices was highly effective. A negligible degradation with only HC and 81% for HC coupled with H2O2 in 60 min for Al-vortex diode compared to 100% degradation in only 5 min for the copper device clearly demonstrates the order of magnitude enhancements establishing dual function due to catalytic activity. Also, pH modification (pH 11) yields enhancement over 300% for Cu-vortex diode. The use of dual function reactors drastically reduces H2O2 do-sage. The overall enhancements in the per pass degradation and cavitation yields were huge, similar to 3000% and 1450% respectively, highlighting the potential of the dual function ca-vitation reactors in real-life applications, not just for increased efficiencies but also for significantly reduced costs.(c) 2023 Institution of Chemical Engineers. Published by Elsevier Ltd. All rights reserved.
Keywords: Advanced oxidation; Degradation; pollution; Technology; Wastewater treatment